2011
DOI: 10.1074/jbc.m111.245886
|View full text |Cite
|
Sign up to set email alerts
|

HNK-1 Glycan Functions as a Tumor Suppressor for Astrocytic Tumor

Abstract: Astrocytic tumor is the most prevalent primary brain tumor. However, the role of cell surface carbohydrates in astrocytic tumor invasion is not known. In a previous study, we showed that polysialic acid facilitates astrocytic tumor invasion and thereby tumor progression. Here, we examined the role of HNK-1 glycan in astrocytic tumor invasion. A Kaplan-Meier analysis of 45 patients revealed that higher HNK-1 expression levels were positively associated with increased survival of patients. To determine the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In contrast, C6 cells transfected with GlcAT-P cDNA (named G14 cells, [20]) express CD57. To verify the blocking capacity of the HNK-1 anti-CD57 antibody (BD) a 24-well transwell chamber system (8 µm pore size; BD Biosciences) was used.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, C6 cells transfected with GlcAT-P cDNA (named G14 cells, [20]) express CD57. To verify the blocking capacity of the HNK-1 anti-CD57 antibody (BD) a 24-well transwell chamber system (8 µm pore size; BD Biosciences) was used.…”
Section: Methodsmentioning
confidence: 99%
“…β-1,6- N -acetylglucosaminyltransferase III suppressed lung metastasis of melanoma cells by inhibiting tumor cell attachment to extracellular matrices in the extravasation stage of metastasis [3]. Recently, it was reported that HNK-1 glycan suppressed astrocytic tumor invasion and metastasis [4]. …”
Section: Two Opposing Roles Of Carbohydrates In Tumor Metastasismentioning
confidence: 99%
“…This antigen has also been found in neuronal cells (32, 33). HNK-1 antigen found on adhesion molecules such as neural cell adhesion molecule (32, 33), MAG (34), L2 (35), P0 (36), GluR2 (37), RPTPβ (38), and CD24 (39) is suggested to modulate adhesion of HNK-1-positive cell types (35). Neurite outgrowth by mouse motor neurons is facilitated by an HNK-1 glycolipid substratum (40).…”
Section: Introductionmentioning
confidence: 99%